Solid electrolyte membrane and all-solid-state battery containing the same

JP7917254B2Active Publication Date: 2026-09-08LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025503156
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-16
Filing Date
2024-04-12
Publication Date
2026-09-08
Estimated Expiration
2044-04-12

AI Technical Summary

Benefits of technology

【0014】 本発明の全固体電池用固体電解質膜は、第1固体電解質粒子及び第2固体電解質粒子を含み、前記第1固体電解質粒子及び第2固体電解質粒子のヤング率、平均粒度及び重量比を調節すると、正極と固体電解質膜の界面及び負極と固体電解質膜の界面接合力が向上し、界面で発生する抵抗を最小化することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007917254000001
    Figure 0007917254000001
  • Figure 0007917254000002
    Figure 0007917254000002
  • Figure 0007917254000003
    Figure 0007917254000003
Patent Text Reader

Abstract

The present invention provides a solid electrolyte membrane for an all-solid-state battery, comprising first solid electrolyte particles and second solid electrolyte particles, the Young's modulus of the first solid electrolyte particles is higher than the Young's modulus of the second solid electrolyte particles; the first solid electrolyte particles and the second solid electrolyte particles have an average particle size (D50) of 1 to 5 μm; The first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 7:3 to less than 2:8, and the present invention relates to a solid electrolyte membrane for an all-solid-state battery and an all-solid-state battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application claims priority under Korean Patent Application No. 10-2023-0063088 dated 16 May 2023, and incorporates all the contents disclosed in the said Korean Patent Application as part of this Specification.

[0002] This invention relates to a solid electrolyte membrane and an all-solid-state battery containing the same. [Background technology]

[0003] From the perspectives of battery capacity, safety, output, scaling up, and miniaturization, various types of batteries are currently being researched that can overcome the limitations of lithium-ion secondary batteries.

[0004] Typically, metal-air batteries, which have a much larger theoretical capacity than lithium-ion batteries; all-solid-state batteries, which pose no risk of explosion in terms of safety; supercapacitors, which offer high output; NaS batteries or RFB (redox flow batteries), which are designed for larger sizes; and thin-film batteries, which are designed for ultra-miniaturization, are among the technologies that are being continuously researched in academia and industry.

[0005] All-solid-state batteries are batteries that replace the liquid electrolyte used in conventional lithium-ion secondary batteries with a solid electrolyte. Because they do not use flammable solvents within the battery, there is no risk of ignition or explosion due to the decomposition reaction of conventional electrolytes, thus significantly improving safety. Furthermore, because lithium (Li) metal or lithium alloy can be used as the negative electrode material, there is an advantage in that the energy density relative to the mass and volume of the battery can be dramatically improved.

[0006] All-solid-state batteries are manufactured by interposing a solid electrolyte membrane between the positive and negative electrodes and then applying high-pressure pressing. At this time, lithium ions (Li) are formed at the interface between the positive electrode and the solid electrolyte membrane, and at the interface between the negative electrode and the solid electrolyte membrane.+ The smoother the movement of ), the more the performance of an all-solid-state battery can be improved. However, when the hardness of a solid electrolyte membrane is high, large resistance to the movement of lithium ions occurs at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane, which may possibly degrade the performance of the all-solid-state battery.

[0007] Accordingly, there is a need for research to minimize the resistance generated at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane, so as to improve the performance of all-solid-state batteries.

Prior Art Document

Patent Document

[0008]

Patent Document 1

Summary of the Invention

Problem to be Solved by the Invention

[0009] The present inventors have completed the present invention after confirming that when the solid electrolyte membrane comprises first solid electrolyte particles and second solid electrolyte particles, and adjusting the Young's modulus, average particle size and weight ratio of the first solid electrolyte particles and the second solid electrolyte particles, the interfacial bonding strength at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane can be improved, and the resistance generated at the interface can be minimized.

[0010] Accordingly, an object of the present invention is to provide a solid electrolyte membrane for an all-solid-state battery, which can reduce resistance generated at the interface between the positive electrode and the solid electrolyte membrane and at the interface between the negative electrode and the solid electrolyte membrane in an all-solid-state battery.

[0011] Another object of the present invention is to provide an all-solid-state battery excellent in life characteristics and rate characteristics by comprising the above-mentioned solid electrolyte membrane.

Means for Solving the Problem

[0012] In order to achieve the above object, The present invention relates to a solid electrolyte membrane for an all-solid-state battery comprising first solid electrolyte particles and second solid electrolyte particles. The Young's modulus of the first solid electrolyte particle is higher than that of the second solid electrolyte particle. The average particle size (D50) of the first and second solid electrolyte particles is 1 to 5 μm. The present invention provides a solid electrolyte membrane for an all-solid-state battery, wherein the first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 7:3 to less than 2:8.

[0013] Furthermore, the present invention is an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between them. The present invention provides an all-solid-state battery in which the solid electrolyte membrane is the solid electrolyte membrane of the present invention. [Effects of the Invention]

[0014] The solid electrolyte membrane for all-solid-state batteries of the present invention comprises first solid electrolyte particles and second solid electrolyte particles. By adjusting the Young's modulus, average particle size, and weight ratio of the first and second solid electrolyte particles, the bonding force between the interface between the positive electrode and the solid electrolyte membrane, and between the negative electrode and the solid electrolyte membrane, can be improved, and the resistance generated at the interface can be minimized.

[0015] Therefore, the all-solid-state battery containing the solid electrolyte membrane of the present invention can have excellent lifespan characteristics and rate characteristics. [Brief explanation of the drawing]

[0016] [Figure 1] These are graphs showing the life characteristics of Example 1, Comparative Example 1, and Comparative Example 2. [Figure 2] This is a graph showing the life characteristics of Comparative Example 4. [Figure 3] These are rate characteristic measurement graphs for Example 1, Comparative Example 2, and Comparative Example 3. [Modes for carrying out the invention]

[0017] The present invention will be described in more detail below.

[0018] The terms and words used in this specification and in the claims should not be interpreted in a manner limited to their ordinary or dictionary meanings, but rather in a manner and concept consistent with the technical idea of ​​the present invention, based on the principle that inventors may appropriately define the concepts of terms in order to best describe their inventions.

[0019] The terms used in this invention are used solely to describe specific embodiments and are not intended to limit the invention. A singular expression includes plural expressions unless the context clearly indicates otherwise. In this invention, terms such as “includes” or “having” are intended to specify the existence of features, figures, stages, operations, components, parts, or combinations thereof described in the specification, and should not be understood to preemptively exclude the existence or possibility of adding one or more other features, figures, stages, operations, components, parts, or combinations thereof.

[0020] Solid electrolyte membrane for all-solid-state batteries This invention relates to a solid electrolyte membrane for all-solid-state batteries. The solid electrolyte membrane comprises first solid electrolyte particles and second solid electrolyte particles. The Young's modulus of the first solid electrolyte particle is higher than that of the second solid electrolyte particle. The average particle size (D50) of the first and second solid electrolyte particles is 1 to 5 μm. The first solid electrolyte particles and the second solid electrolyte particles may be mixed in a weight ratio of 7:3 to less than 2:8.

[0021] The solid electrolyte membrane for an all-solid-state battery of the present invention comprises first solid electrolyte particles and second solid electrolyte particles. The Young's modulus of the first and second solid electrolyte particles are different, and the Young's modulus of the first solid electrolyte particles may be higher than that of the second solid electrolyte particles. By including different types of solid electrolyte particles with different Young's moduli, the Young's modulus of the solid electrolyte membrane can be adjusted. Therefore, the resistance generated at the interface between the positive electrode and the solid electrolyte membrane and the interface between the negative electrode and the solid electrolyte membrane of the all-solid-state battery can be reduced, thereby providing an all-solid-state battery with improved lifespan and rate characteristics.

[0022] The Young's modulus of the first solid electrolyte particles may be 40 to 80 GPa, preferably 40 to 60 GPa, and most preferably 40 to 50 GPa. Generally, the higher the Young's modulus of the particles, the harder and less prone to breakage they are. By having the first solid electrolyte particles have a Young's modulus within this range, the solid electrolyte membrane can maintain its shape even when volume changes occur during charging and discharging of the all-solid-state battery.

[0023] Furthermore, the Young's modulus of the second solid electrolyte particles may be 5 to 30 GPa, preferably 10 to 25 GPa, and most preferably 15 to 20 GPa. Having a Young's modulus within this range of the second solid electrolyte particles allows for easy deformation under high pressure, and can result in excellent bonding between the solid electrolyte membrane and the electrode. In addition, the second solid electrolyte particles are located between the first solid electrolyte particles, minimizing pores, facilitating lithium ion movement, and playing a role in improving the interfacial bonding strength between the solid electrolyte membrane and the electrode.

[0024] The difference in Young's modulus between the first solid electrolyte particles and the second solid electrolyte particles may be 15 to 50 GPa, preferably 20 to 40 GPa. If the difference in Young's modulus is less than 15 GPa, it is possible that either the Young's modulus of the first solid electrolyte particles is low or the Young's modulus of the second solid electrolyte particles is high. If the Young's modulus of the first solid electrolyte particles is low and the difference in Young's modulus is less than 15 GPa, the physical rigidity of the solid electrolyte membrane may decrease. If the Young's modulus of the second solid electrolyte particles is high, the effect of improving the interfacial bonding between the solid electrolyte membrane and the electrode cannot be expected. Furthermore, if it exceeds 40 GPa, the Young's modulus of the first solid electrolyte particles becomes high, which may reduce the interfacial bonding force between the solid electrolyte membrane and the electrode, and thus reduce the interfacial resistance.

[0025] Furthermore, the average particle size (D50) of the first and second solid electrolyte particles is the same and may be 1 to 5 μm, preferably 2 to 3 μm. If the average particle size (D50) of the first and second solid electrolyte particles is less than 1 μm, dispersion of the first and second solid electrolyte particles is not easy during the manufacturing of the solid electrolyte membrane, and a solid electrolyte membrane with a non-uniform surface may be manufactured. This may lead to a problem in which the performance of the all-solid-state battery containing it is reduced. In addition, by having the average particle size within the above range of the first and second solid electrolyte particles, dispersion is easy during the slurry process in the manufacturing process of the solid electrolyte membrane, making it possible to manufacture an electrolyte membrane with a uniform surface.

[0026] The first solid electrolyte particles and the second solid electrolyte particles may be mixed in a weight ratio of 7:3 to less than 2:8, preferably in a weight ratio of 6:4 to 4:6, and most preferably in a weight ratio of 5:5. If the content of the first solid electrolyte particles exceeds the above range, the Young's modulus of the solid electrolyte membrane becomes excessively high, reducing the interfacial bonding force between the solid electrolyte membrane and the electrode, which may reduce the lifespan characteristics of the all-solid-state battery containing it. On the other hand, if the content of the first solid electrolyte particles is below the above range, the ionic conductivity of the solid electrolyte membrane may decrease, increasing its resistance, which may reduce the lifespan characteristics and rate characteristics of the all-solid-state battery containing it.

[0027] In the present invention, the Young's modulus of the solid electrolyte membrane may be 20 to 40 GPa, preferably 25 to 35 GPa. The solid electrolyte membrane of the present invention comprises first solid electrolyte particles and second solid electrolyte particles, wherein the Young's modulus of the first solid electrolyte particles is higher than that of the second solid electrolyte particles, the average particle size (D50) of the first and second solid electrolyte particles is 1 to 5 μm, and the first and second solid electrolyte particles are mixed in a weight ratio of 7:3 to less than 2:8. The second solid electrolyte particles have a low Young's modulus and are brittle, and the second solid electrolyte particles are located between the first solid electrolyte particles, minimizing the space, i.e., pores, formed between the first solid electrolyte particles. This improves the interfacial bonding force between the solid electrolyte membrane and the electrode, and can reduce resistance to lithium ion transfer. In other words, it can reduce the interfacial resistance generated at the interface between the solid electrolyte membrane and the electrode. This can improve the lifespan and rate characteristics of an all-solid-state battery containing it.

[0028] Even if a solid electrolyte membrane containing one type of solid electrolyte has the same Young's modulus as in the present invention, it is not possible to minimize the space formed between the solid electrolyte particles, and therefore the effect of reducing interfacial resistance cannot be obtained.

[0029] The first solid electrolyte particles and the second solid electrolyte particles may be one or more selected from the group consisting of sulfide-based solid electrolytes, polymer-based solid electrolytes, and oxide-based solid electrolytes, and preferably a sulfide-based solid electrolyte.

[0030] Furthermore, the first solid electrolyte particles and the second solid electrolyte particles may be identical to each other, except for their differing Young's moduli.

[0031] The sulfide-based solid electrolyte contains sulfur (S) and has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS glass or Li-PS glass ceramic.

[0032] Specifically, the sulfide-based solid electrolyte may contain one or more selected from the group consisting of Li6PS5Cl, Li6PS5Br, Li6PS5I, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2S5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, and Li2S-GeS2-ZnS, and preferably contains one or more selected from the group consisting of Li6PS5Cl, Li6PS5Br, and Li6PS5I. The Li6PS5Cl, Li6PS5Br, and Li6PS5I mentioned above may be argyrodite-type solid electrolytes. Furthermore, the sulfide-based solid electrolyte may be in a form doped with trace amounts of elements; for example, Li6PS5Cl may be further doped with bromine (Br).

[0033] The aforementioned polymer solid electrolyte is a composite of a lithium salt and a polymer resin, that is, a polymer electrolyte material formed by adding a polymer resin to a solvated lithium salt, and is approximately 1 x 10⁻⁶ -7 S / cm or more, preferably about 1 x 10 -5 It can exhibit ionic conductivity of S / cm or higher.

[0034] Non-limiting examples of the polymer resin include polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide, phosphate ester polymers, polyeditation lysine (agitation lysine), polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionic dissociation groups, and the polymer resin may include one or more of these. Further, examples of the polymer electrolyte as the polymer resin include branched copolymers obtained by copolymerizing a PEO (poly ethylene oxide) main chain with an amorphous polymer such as PMMA, polycarbonate, polysiloxane (pdms) and / or phosphazene as a comonomer, comb-like polymer resins, crosslinked polymer resins, and the like, and the polymer electrolyte may contain one or more of these.

[0035] In the polymer solid electrolyte, the aforementioned lithium salt is an ionizable lithium salt, represented by Li + X - . There is no particular limitation on the anion of such a lithium salt, and examples include F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C- CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - , (CF3CF2SO2)2N - Examples include the following.

[0036] The oxide-based solid electrolyte may contain oxygen (O) and have the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. For example, LLTO compounds, Li6La2CaTa2O 12 Li6La2ANb2O 12 (A is Ca or Sr), Li2Nd3TeSbO 12 Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li1 +x Ti 2-x Al x Si y (PO4) 3-y (Here, 0≦x≦1, 0≦y≦1), LiAl x Zr 2-x (PO4)3 (where 0≦x≦1), LiTi x Zr 2-x (PO4)3 (where 0 ≤ x ≤ 1), may contain one or more compounds selected from LISICON compounds, LIPON compounds, perovskite compounds, NASICON compounds, and LLZO compounds.

[0037] The solid electrolyte membrane may further include a binder. The type of binder is not particularly limited, as long as it is used in the industry.

[0038] For example, acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butadiene rubber (BR), styrene-butadiene-styrene copolymer (SBS), polybutadiene (PAN), styrene-ethylene / butylene-styrene block copolymer (SEBS), silicone rubber (SR), hydrogenated nitrile butadiene rubber (HNBR), poly(ethylene vinyl acetate) (PEVA), poly(methyl methacrylate) (PMMA), polyisobutene (PIB), polyacrylate, etc. may be used, but are not limited to these.

[0039] The binder may be present in an amount of 0.5 to 5% by weight relative to the total weight of the solid electrolyte membrane. Furthermore, the combined weight of the first and second solid electrolytes may be present in an amount of 95 to 99.5% by weight relative to the total weight of the solid electrolyte membrane. By including the solid electrolyte and binder as described above, it is possible to manufacture a solid electrolyte membrane for all-solid-state batteries that can be maintained in film form while minimizing the binder content, which acts as a resistive factor on ionic conductivity.

[0040] The solid electrolyte membrane for an all-solid-state battery of the present invention can be manufactured by dispersing the first solid electrolyte particles and the second solid electrolyte particles in a solvent to produce a slurry, applying the slurry to one surface of a release film, drying it, and then removing the release film. The slurry may further contain a binder.

[0041] The first solid electrolyte particles, the second solid electrolyte particles, and the binder are as described above.

[0042] The solvent is not particularly limited in type, as long as it can disperse the first solid electrolyte particles, the second solid electrolyte particles, and the binder. For example, xylene, hexane, benzene, anisole, isobutyl isobutyrate, toluene, and butyl butyrate can be used.

[0043] The ionic conductivity of the solid electrolyte membrane for the all-solid-state battery may be 1 to 1.6 mS / cm. The ionic conductivity may be measured at room temperature (25°C).

[0044] All solid state battery The present invention relates to an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between them, wherein the solid electrolyte membrane may be the solid electrolyte membrane of the present invention as described above.

[0045] The all-solid-state battery is a lithium secondary battery, and there are no restrictions on whether it is a positive or negative electrode. It may be a lithium-air battery, a lithium oxide battery, a lithium-sulfur battery, or a lithium metal battery.

[0046] The positive electrode may include a positive electrode current collector and a positive electrode active material coated on one or both sides of the positive electrode current collector.

[0047] The positive electrode current collector is for supporting the positive electrode active material and is not particularly limited as long as it has excellent conductivity and is electrochemically stable in the voltage range of the lithium secondary battery. For example, the positive electrode current collector may be any one metal selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver. As the alloy, an aluminum-cadmium alloy may be preferably used. Other materials such as calcined carbon, a non-conductive polymer surface-treated with a conductive material, or a conductive polymer may also be used.

[0048] The positive electrode current collector can have fine irregularities formed on its surface to strengthen its bonding force with the positive electrode active material, and may be used in various forms such as film, sheet, foil, mesh, net, porous material, foam, nonwoven fabric, etc.

[0049] The positive electrode active material may selectively include a conductive material and a binder.

[0050] The positive electrode active material may vary depending on the type of all-solid-state battery. For example, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as O4 (0 ≤ x ≤ 0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x Ni-site type lithium nickel oxide represented by O2 (M=Co, Mn, Al, Cu, Fe, Mg, B or Ga; 0.01≦x≦0.3); chemical formula LiMn 2-x M x Lithium manganese composite oxide represented as O2 (M=Co, Ni, Fe, Cr, Zn, or Ta; 0.01≦x≦0.1) or Li2Mn3MO8 (M=Fe, Co, Ni, Cu, or Zn); LiNi x Mn 2-x Lithium manganese composite oxide with a spinel structure represented by O4; LiCoPO4; LiFePO4; elemental sulfur (S8); Li2S n (n=1), organosulfur compounds or carbon-sulfur polymers ((C2S x ) n This may include, but is not limited to, sulfur series compounds such as (x=2.5~50, n=2).

[0051] The conductive material electrically connects the electrolyte and the positive electrode active material, and acts as a pathway for electrons to move from the current collector to the positive electrode active material. It can be used without limitation as long as it does not cause chemical changes in lithium secondary batteries and is porous and conductive.

[0052] For example, the conductive material can be a porous carbon-based material, such as carbon black, graphite, graphene, activated carbon, carbon fiber, metallic fibers such as metal mesh; metallic powders such as copper, silver, nickel, and aluminum; or organic conductive materials such as polyphenylene derivatives. The conductive materials can be used individually or in combination.

[0053] Currently, commercially available conductive materials include the acetylene black series (products from Chevron Chemical Company or Gulf Oil Company, etc.), the Ketjen Black EC series (products from Armak Company), Vulcan XC-72 (products from Cabot Company), and Super P (products from MMM). Examples include acetylene black, carbon black, and graphite.

[0054] Furthermore, the positive electrode may further include a binder, which enhances the bonding force between the components constituting the positive electrode and between them and the current collector. Any binder known in the industry can be used.

[0055] For example, the binder may be one, a mixture of two or more, or a copolymer selected from the group consisting of: fluororesin binders containing polyvinylidenefluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber binders containing styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose binders containing carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyalcohol binders; polyolefin binders containing polyethylene or polypropylene; polyimide binders; polyester binders; and silane binders.

[0056] The negative electrode may include a negative electrode current collector and a negative electrode active material located on the negative electrode current collector. Furthermore, the negative electrode, like the positive electrode, may optionally include a conductive material and a binder. In this case, the negative electrode current collector, conductive material, and binder are as described above.

[0057] The aforementioned negative electrode active material is lithium ion (Li + Any substance that can reversibly intercalate or deintercalate lithium, or react with lithium ions to reversibly form lithium-containing compounds, is acceptable.

[0058] For example, the negative electrode active material is one or more carbon-based materials, Si-based materials, Li selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, Ketjen black, Super-P, graphene, and fibrous carbon. x Fe2O3 (0 ≤ x ≤ 1), Li x WO2(0≦x≦1), Sn x Me 1-xMe' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0<x≦1; 1≦y≦3; 1≦z≦8) and other metal composite oxides; lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄, Bi₂O₅; conductive polymers such as polyacetylene; Li-Co-Ni based materials; titanium oxides; lithium titanium oxides, but are not limited thereto.

[0059] Further, the negative electrode may comprise a negative electrode current collector and a coating layer comprising metal-carbon composite particles located on the negative electrode current collector. This may mean an anodeless structure that does not contain a negative electrode active material.

[0060] During charging of the all-solid-state battery, lithium ions may pass through the coating layer to reach the surface of the negative electrode current collector, and electrodeposit there to form a lithium metal layer.

[0061] The metal-carbon composite particles may have a form where carbon particles and metal particles are adhered to each other, or one of the particles has the other coated on its surface, and may be physically or chemically bonded.

[0062] The carbon particles may comprise natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, summer black, carbon nanotubes, fullerene, carbon fiber, and fluorocarbon.

[0063] The aforementioned metal particles are lithiophilic metals, such as Ni, Cu, Ag, Au, Pt, Al, Zn, and Bi, and may be one or more of these in combination. Introducing these lithium-philic metals is advantageous for forming a stable and uniform lithium layer on the surface of the current collector.

[0064] The negative electrode may be manufactured by mixing a binder solution and the composite particles to produce a slurry for forming a coating layer, and then applying and drying the slurry onto a negative electrode current collector. In this case, the binder may be a conventional binder used in the industry.

[0065] The manufacturing of the all-solid-state battery is not particularly limited in the present invention, and known methods can be used.

[0066] As an example, a solid electrolyte membrane is placed between the positive and negative electrodes, and then the cell is assembled by compression molding. After the assembled cell is placed inside an outer packaging material, it is sealed by heat compression or the like. As the outer packaging material, laminate packs made of aluminum, stainless steel, etc., or metal containers such as cylindrical or rectangular containers can be used.

[0067] As an example, the positive and negative electrodes are manufactured in the form of a slurry composition containing the respective electrode active material, solvent, and binder, and then coated and dried in a slurry coating process.

[0068] Methods for coating the electrode slurry onto a current collector include distributing the electrode slurry onto the current collector and then uniformly dispersing it using a doctor blade, die casting, comma coating, and screen printing. Alternatively, the electrode slurry can be formed on a separate substrate and then bonded to the current collector by pressing or lamination. In this case, the thickness of the final coating can be adjusted by adjusting the concentration of the slurry solution or the number of coatings.

[0069] The drying process involves removing solvent and moisture from the slurry coated on the metal current collector in order to dry it, and may vary depending on the solvent used. For example, it is performed in a vacuum oven at 50-200°C. Drying methods include, for example, drying with hot air, hot air, low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams. While there are no particular limitations on drying time, it is usually carried out in the range of 30 seconds to 24 hours.

[0070] The drying process may be followed by a cooling process, which may involve slow cooling to room temperature to allow for proper recrystallization of the binder.

[0071] Furthermore, if necessary, after the drying process, a rolling process can be performed in which the electrodes are passed between two high-temperature heated rolls and compressed to a desired thickness in order to increase the capacitance density of the electrodes and increase the adhesion between the current collector and the active material. The rolling process is not particularly limited in this invention, and any known rolling process (pressing) is possible. For example, it may be performed by passing the electrodes between rotating rolls or by using a flat plate press.

[0072] The shape of the all-solid-state battery is not particularly limited and can be in various shapes such as cylindrical, stacked, or coin-shaped.

[0073] The following are preferred embodiments to aid in understanding the present invention. However, these embodiments are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the present invention and the technical concept, and that such changes and modifications naturally fall within the scope of the attached claims.

[0074] <All-solid-state battery manufacturing> Example 1. Argyrodite (Li6PS5Cl) with a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm was used as the first solid electrolyte particle. Argyrodite (Li6PS5Cl) with a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm was used as the second solid electrolyte particle. Butadiene rubber was used as the binder.

[0075] A slurry was prepared by adding the first solid electrolyte particles, the second solid electrolyte particles, and a binder to a butyl butyrate solvent. At this time, the weight ratio of the first solid electrolyte particles to the second solid electrolyte particles was 5:5. Also, the weight ratio of the first solid electrolyte particles, the second solid electrolyte particles, and the binder was 49:49:2.

[0076] Polyethylene terephthalate was used as a release film, and the slurry was coated onto the release film using a bar coater. After drying at room temperature for 5 hours, the release film was removed to produce a solid electrolyte membrane for an all-solid-state battery. The Young's modulus of the solid electrolyte membrane for the all-solid-state battery was 30 GPa.

[0077] A positive electrode was manufactured by mixing a positive electrode active material (NCM 811), a conductive material (carbon fiber), a solid electrolyte (Li6PS5Cl), and a binder (polytetrafluoroethylene) in a weight ratio of 84:0.2:14.8:1, applying the mixture to a positive electrode current collector, and then rolling it.

[0078] The negative electrode was manufactured by coating a 150 μm thick mixture of negative electrode active material (carbon black) and binder (polyvinylidene fluoride) onto a 10 μm thick SUS (stainless steel) material, which served as the negative electrode current collector.

[0079] A solid-state battery was manufactured by interposing the solid electrolyte membrane between the positive electrode and the negative electrode, and a drive pressure of 10 MPa was applied using a jig.

[0080] Comparative Example 1. An all-solid-state battery was manufactured in the same manner as in Example 1, except that an argyrodite (Li6PS5Cl) with a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm was used as the first solid electrolyte particle, no second solid electrolyte was used, and the first solid electrolyte particle was used in twice the amount compared to Example 1. The Young's modulus of the solid electrolyte membrane for the all-solid-state battery was 42 GPa.

[0081] Comparative Example 2. An all-solid-state battery was manufactured in the same manner as in Example 1, except that argyrodite (Li6PS5Cl) with a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm was used as the second solid electrolyte particle, the first solid electrolyte particle was not used, and the second solid electrolyte particle was used at twice the content compared to Example 1. The Young's modulus of the solid electrolyte membrane for the all-solid-state battery was 18 GPa.

[0082] Comparative Example 3. An all-solid-state battery was manufactured in the same manner as in Example 1, except that the first solid electrolyte particles and the second solid electrolyte particles were mixed in a weight ratio of 2:8.

[0083] Comparative Example 4. An all-solid-state battery was manufactured in the same manner as in Example 1, except that argyrodite (Li6PS5Cl) with an average particle size (D50) of 0.6 μm was used as the second solid electrolyte particle.

[0084] Experimental Example 1. Measurement of Life Characteristics of All-Solid-State Batteries The life characteristics of the all-solid-state batteries described in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4 were measured.

[0085] Lifetime characteristics were measured by charging the all-solid-state batteries of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4 at 60°C in CCCV mode at 0.33C until the voltage reached 4.25V, discharging them to 3.0V with a constant current, and measuring the capacity retention rate after 100 charge-discharge cycles.

[0086] The results for Example 1, Comparative Example 1, and Comparative Example 2 are shown in Figure 1.

[0087] In the results shown in Figure 1, the lifetime characteristics of Example 1, an all-solid-state battery containing the solid electrolyte membrane of the present invention, were measured with the best performance.

[0088] Comparative Example 1 contained only argyrodite (Li6PS5Cl) with a Young's modulus of 42 GPa and an average particle size (D50) of 2.5 μm as the solid electrolyte particles, and did not contain any second solid electrolyte particles. Comparative Example 1 showed that the life characteristics of the all-solid-state battery deteriorated because the bonding force at the interface between the solid electrolyte membrane and the positive electrode, and at the interface between the solid electrolyte membrane and the negative electrode, was very low.

[0089] Comparative Example 2 contained only argyrodite (Li6PS5Cl) with a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm as the solid electrolyte particles, and did not contain the first solid electrolyte particles. Comparative Example 2 showed that the low ionic conductivity of the solid electrolyte membrane increased the resistance of the all-solid-state battery, resulting in a deterioration of the all-solid-state battery's lifespan characteristics.

[0090] The results of Comparative Example 4 are shown in Figure 2.

[0091] Comparative Example 4 used argyrodite (Li6PS5Cl) with an average particle size (D50) of 0.6 μm as the second solid electrolyte particle. During the manufacturing of the solid electrolyte membrane, the dispersion of the second solid electrolyte particle was not easy, resulting in the production of a non-uniform solid electrolyte membrane. Consequently, the life characteristics of the all-solid-state battery were extremely poor.

[0092] Experimental Example 2. Measurement of Rate Characteristics of All-Solid-State Batteries The rate characteristics of the all-solid-state batteries described in Example 1, Comparative Example 2, and Comparative Example 3 were measured.

[0093] Rate characteristics were measured by charging at 3.0-4.25V and 0.1C, and discharging at 0.1, 0.33, 0.5, and 1C.

[0094] The results for Example 1, Comparative Example 2, and Comparative Example 3 are shown in Figure 3.

[0095] As shown in the results in Figure 3, Example 1, an all-solid-state battery containing the solid electrolyte membrane of the present invention, showed excellent rate characteristics.

[0096] Comparative Example 2 contained only argyrodite (Li6PS5Cl) with a Young's modulus of 18 GPa and an average particle size (D50) of 2.5 μm as the solid electrolyte, and did not contain the first solid electrolyte particles. In Comparative Example 2, the ionic conductivity of the solid electrolyte membrane was low, which increased the resistance of the all-solid-state battery, resulting in poor rate characteristics for the all-solid-state battery.

[0097] Comparative Example 3 involved mixing the first solid electrolyte particles and the second solid electrolyte particles in a weight ratio of 2:8. While it showed an improvement in rate characteristics compared to Comparative Example 2, it did not achieve the same rate characteristics as Example 1.

[0098] This includes a first solid electrolyte particle and a second solid electrolyte particle, The Young's modulus of the first solid electrolyte particle is higher than that of the second solid electrolyte particle. The average particle size (D50) of the first and second solid electrolyte particles is 1 to 5 μm. It was confirmed that an all-solid-state battery containing a solid electrolyte membrane for all-solid-state batteries, in which the first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 7:3 to less than 2:8, has excellent effects on lifespan characteristics and rate characteristics.

[0099] This effect is attributed to the fact that the solid electrolyte membrane minimizes the resistance generated at the interface between the positive electrode and the solid electrolyte membrane, and at the interface between the negative electrode and the solid electrolyte membrane.

Claims

1. A solid electrolyte membrane for an all-solid-state battery, comprising first solid electrolyte particles and second solid electrolyte particles, The Young's modulus of the first solid electrolyte particle is higher than that of the second solid electrolyte particle. The average particle size (D50) of the first and second solid electrolyte particles is 1 μm or more and 5 μm or less. The first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 7:3 to less than 2:

8. A solid electrolyte membrane for all-solid-state batteries, wherein the difference in Young's modulus between the first solid electrolyte particle and the second solid electrolyte particle is 15 GPa or more and 50 GPa or less.

2. The solid electrolyte membrane according to claim 1, wherein the Young's modulus of the first solid electrolyte particle is 40 GPa or more and 80 GPa or less.

3. The solid electrolyte membrane according to claim 1, wherein the Young's modulus of the second solid electrolyte particle is 5 GPa or more and 30 GPa or less.

4. The solid electrolyte membrane according to claim 1, wherein the difference in Young's modulus between the first solid electrolyte particle and the second solid electrolyte particle is 20 GPa or more and 40 GPa or less.

5. The solid electrolyte membrane according to claim 1, wherein the particle size (D50) of the first solid electrolyte particles and the second solid electrolyte particles is 2 μm or more and 3 μm or less.

6. The solid electrolyte membrane according to claim 1, wherein the first solid electrolyte particles and the second solid electrolyte particles are mixed in a weight ratio of 6:4 to 4:

6.

7. The solid electrolyte membrane according to claim 1, wherein the first solid electrolyte particles and the second solid electrolyte particles include one or more selected from the group consisting of sulfide-based solid electrolytes, polymer-based solid electrolytes, and oxide-based solid electrolytes.

8. The solid electrolyte membrane according to claim 7, wherein the first solid electrolyte particles and the second solid electrolyte particles are sulfide-based solid electrolytes.

9. The solid electrolyte membrane according to claim 1, wherein the solid electrolyte membrane further comprises a binder.

10. The solid electrolyte membrane according to claim 9, wherein the binder is contained in an amount of 0.5% by weight or more and 5% by weight or less relative to the total weight of the solid electrolyte membrane.

11. This is an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between them. The solid electrolyte membrane is the solid electrolyte membrane described in any one of claims 1 to 9, in an all-solid-state battery.

12. The negative electrode includes a negative electrode current collector and a negative electrode active material located on the negative electrode current collector; or The all-solid-state battery according to claim 11, comprising a negative electrode current collector and a coating layer containing metal-carbon composite particles located on the negative electrode current collector.

Citation Information

Patent Citations

  • Composite solid electrolyte and all-solid battery

    JP2020027701A

  • All solid secondary battery and method of manufacturing the same

    KR1020210087919A

  • KR2021-0087919

  • Composite electrode containing sulfide-based solid electrolyte and all-solid-state battery using same

    US20210013541A1

  • Solid electrolyte and battery using same

    WO2020100465A1